Report of the glaciological field party in the Soer Rondane Mountains region, 1989-1990 Summer Season (JARE-31) - Motoyama, H.; Azuma, N.; Decleir, H.; Huybrechts, Philippe (1990)
Summer party of the 31st Japanese Antarctic Research Experdition (JARE-31) carried out maintenance of automatic meteorological stations, glaciological observation, and drilling test for"Antarctic Climate Research (ACR)" project from late December 1989 to January 1990 around the Soer Rondane Mountains region. This party is constituted by four glaciologists includingtwo Belgian observers and one JARE-30 member.Three prototypes of electromechanical ice drill for deep core sampling using antifreezing liquid were successfully tested on a bare glacier at Jenningsbreen. On the same glacier, dynamicsof glacier movement were studied by Belgian observers. Mass balance measurement were conducted on Goosenbreen of Brattnipane.Two helicopters were employed for geological and topographical survey in the Soer Rondane region, so that we were able to fly to Nansenisen, south of Soer Rondane, and to obtainsurface bare ice within dust band (volcanic ash?).